Implementasi Pembelajaran Akidah dan Akhlak dalam Pembentukan Karakter Religius Peserta Didik Kelas VIII di SMP NU Kajen - Solahur Rizqi; Ubed Badrudin Kamal; Mohammad Syaifuddin (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study aims to analyze the implementation of Akidah Akhlak learning in developing religious character among 8th-grade students at SMP NU Kajen. Religious character serves as the foundation of Islamic education in facing moral degradation challenges in the globalization era. Using a descriptive qualitative approach, data were collected through participatory observation, in-depth interviews, and documentation study. The results show that Akidah Akhlak learning is implemented through: (1) planning (integrated curriculum development and character-based lesson plans), (2) implementation (experiential learning, teacher modeling, and habituation), and (3) evaluation (authentic assessment). The formation of religious character is manifested in five dimensions: faith, worship, morals, knowledge, and practice. Supporting factors include pesantren-based school environment, parental support, and extracurricular religious programs, while inhibiting factors include social media influence, limited learning time, and diverse student backgrounds.